Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s12987-017-0058-1
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid (CSF) biomarkers of iron status are associated with CSF viral load, antiretroviral therapy, and demographic factors in HIV-infected adults

Abstract: BackgroundHIV-associated neurocognitive disorder (HAND) remains common, despite antiretroviral therapy (ART). HIV dysregulates iron metabolism, but cerebrospinal fluid (CSF) levels of iron and iron-transport proteins in HIV-infected (HIV+) persons are largely unknown. The objectives of this study were to characterize CSF iron-related biomarkers in HIV+ adults and explore their relationships to known predictors of HAND.MethodsWe quantified total iron, transferrin and heavy-chain (H)-ferritin by immunoassay in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 95 publications
2
24
0
Order By: Relevance
“…We demonstrated in the cell culture model that Hft can limit Sema4A‐mediated cytotoxicity. Hft is not only present in the human CSF (Patton et al, ), but in support of the notion that it could impact cytotoxicity has been shown to be protective in HIV persons. Taken together, these findings indicate a role for Sema4A in the pathophysiology of demyelination and a clear relationship between Tim‐1, iron uptake in oligodendrocytes, and the immune system.…”
Section: Discussionmentioning
confidence: 72%
“…We demonstrated in the cell culture model that Hft can limit Sema4A‐mediated cytotoxicity. Hft is not only present in the human CSF (Patton et al, ), but in support of the notion that it could impact cytotoxicity has been shown to be protective in HIV persons. Taken together, these findings indicate a role for Sema4A in the pathophysiology of demyelination and a clear relationship between Tim‐1, iron uptake in oligodendrocytes, and the immune system.…”
Section: Discussionmentioning
confidence: 72%
“…Iron homeostasis is essential for maintenance of mitochondrial function and energy production in the brain, as neural tissues have extremely high metabolic demand, and iron is a key component of the molecular complexes that constitute the electron transport chain. Furthermore, by virtue of its ability to readily accept and donate electrons, iron is a required cofactor for a very large number of fundamental metabolic processes, including synthesis of DNA, heme, monoamine neurotransmitters, and myelin Patton et al 2017;Puig et al 2017). However, iron that is not tightly proteinbound is highly reactive and generates oxidative stress by catalyzing free radical reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted November 6, 2020. ; https://doi.org/10.1101/2020.11.04.20199760 doi: medRxiv preprint CSF iron-biomarker levels were determined using commercially available assay kits according to the manufacturer's protocol [17]. Concentrations of inflammatory cytokines and chemokines were measured in CSF by commercial, high-sensitivity multiplex assay Table S1).…”
Section: Quantification Of Csf Iron Biomarkers and Inflammationmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted November 6, 2020. ; https://doi.org/10.1101/2020.11.04.20199760 doi: medRxiv preprint As iron homeostasis in HAND is a new area of investigation, and we previously associated CSF H-ferritin and transferrin with comorbidity and zidovudine use, we also stratified H-ferritin and transferrin models by comorbidity and zidovudine use, respectively, and tested for multiplicative interactions between these variables [17]. Adjustment for self-reported race/ethnicity did not significantly alter results, and the GDS includes corrections for demographic norms, so race/ethnicity was not included in the final models.…”
Section: Quantification Of Csf Iron Biomarkers and Inflammationmentioning
confidence: 99%